Analisis pemetaan media tentang pembiayaan rahn di Indonesia dengan NVivo : Studi literatur review - Bagaskara, Doni Yusuf; Rohmadi, Rohmadi (Journal of Management and Digital Business, 2024)
This research aims to determine a media mapping analysis of Rahn Financing in Indonesia using the NVivo tool. This research uses qualitative methodology assisted by NVivo and a literature review. Several data analysis techniques in this research include firstly mapping the number of news article codes based on qualitative analysis such as meaning, objectives, terms and conditions, and laws, regarding "Rahn" using NVivo 14 software, secondly mapping the visualization results with hierarchical diagrams and testing the correlation between articles. Media uses qualitative analysis, thirdly mapping the research topic with Worldcloud or a collection of words often discussed in media articles, and finally testing the significant value between media articles to determine the correlation size around the topic "Rahn". The results of this research indicate that the topics often discussed in media articles regarding Rahn Financing are goals and understanding. Meanwhile, media articles rarely discuss objectives and terms and conditions regarding Rahn Financing. The implications of this research show that analysis using NVivo and Literature Review tools can be a recommendation for increasing public literacy regarding financial financing through media articles by looking at frequently discussed topics.